On the atmospheric structure and fundamental parameters of red supergiants. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Wittkowski, M.; Arroyo-Torres, B.; Marcaide, J. M.; Abellan, F. J.; Chiavassa, A.; Freytag, B.; Scholz, M.; Wood, P. R.; Hauschildt, P. H.
Abstract: We present near-infrared spectro-interferometric studies of red supergiant (RSG) stars using the VLTI/AMBER instrument, which are compared to previously obtained similar observations of AGB stars. Our observations indicate spatially extended atmospheric molecular layers of water vapor and CO, similar as previously observed for Mira stars. Data of VY~CMa indicate that the molecular layers are asymmetric, possibly clumpy. Thanks to the spectro-interferometric capabilities of the VLTI/AMBER instrument, we can isolate continuum bandpasses, estimate fundamental parameters of our sources, locate them in the HR diagram, and compare their positions to recent evolutionary tracks. For the example of VY CMa, this puts it close to evolutionary tracks of initial mass 25-32 M ⊙ . Comparisons of our data to hydrostatic model atmospheres, 3d simulations of convection, and 1d dynamic model atmospheres based on self-excited pulsation models indicate that none of these models can presently explain the observed atmospheric extensions for RSGs. The mechanism that levitates the atmospheres of red supergiant is thus a currently unsolved problem.